Adhesion science - Comyn, John, 1942- (Royal Society of Chemistry, 2021)
"The use of adhesives is widespread and growing. There are few modern artefacts, from simple food packing to complex jumbo jets, that are without this means of adhesive joining. Fully updated and revised, Adhesion Science 2nd Edition provides an illuminating account of the science underlying the use of adhesives; technology fundamental to the science of coatings and composite materials, and to the performance of all types of bonded structures. This book guides the reader through essential polymer science to the chemistry of adhesives currently in use. It discusses surface preparation for adhesive bonding, the use of primers and coupling agents and includes a simple guide on stress distribution joints and considerations for testing. Adhesion Science also examines the interaction of adhesives and the environment, including an analysis of the resistance of joints to water, oxygen and ultra-violet light. This book is a comprehensive introduction to the chemistry of adhesives ideal not only for chemists, but any students with a background in physical or materials science."--Publisher's description.
Keywords: Adhesion.; Adhesives.; elektronické knihy; electronic books